Praxis in the past: Approaches to the intervention of the architectural heritage in Lima - Bonilla Polanco, Pamela (2018)
A monument of cultural heritage is a construction that has an important value in aesthetic, scientific and historical terms for a specific group of people and, therefore, its safeguard must be guaranteed in order to preserve it for the future generation’s knowledge. In the particular case of Lima, a large number of such buildings are damaged and under the risk of disappearing if no action is soon taken. Consequently, this is an outstanding issue of study that involves different professional fields. Thus, the following article will analyze the urbanist-architectural aspect and investigates models of intervention in the built heritage from a conceptual, methodological and proactive approach. From the viewpoint of each of the architects, three recognizable interventions in urban space will be presented, each with a varying degree of interference, which have been made recently. We have developed the following cases: St Mark’s Mansion, whose patios were the location of different historical issues; Barranco’s old Municipal Market, an important and representative building regarding citizen’s memory; and Cori Wasi Cultural Centre, an integrating element of the urban complex of the Arequipa Avenue.